Are households shifting toward cleaner cooking fuel? Empirical evidence from India during 2005–2021 - Timilsina, Raja Rajendra; Rahut, Dil B.; Gautam, Madhu Sudan; Mishra, Raman; Sonobe, Tetsushi (Frontiers in Environmental Economics, 2023)
The natural environment is negatively impacted by the daily fuel use for domestic purposes, particularly in developing nations with large populations, such as India, where biomass is the primary source of fuel for household cooking. However, a greater understanding is needed about the trends, patterns, and factors affecting household energy consumption and choice in India over the past two decades. The National Family Health Survey (NFHS) data from the years 2005–2006, 2015–2016, and the most recent year 2019–21 are used in this study to empirically demonstrate that characteristics including gender, education, capital, social status, and geography have significant influence on a household's decision to use cleaner energy. The results report that homes in rural regions, the poorest and most impoverished households, those headed by women, and without formal education have been unable to switch to cleaner fuels such as liquid petroleum gas (LPG) over time. As the study suggests that increasing income levels and education can lead to a shift toward cleaner household energy consumption, policies promoting economic growth and education can reduce greenhouse gas emissions from household energy consumption. Thus, policies like subsidies in LPG and electricity shall explicitly aim to assist impoverished households and lower-income families in enhancing their accessibility and affordability options for cleaner energy sources. The research underscores the significance of directing efforts towards the economically disadvantaged segments of society, guaranteeing their access to more environmentally friendly energy sources.